Efeito do Uso do Estabilizador Active Ankle System. na Altura do Salto Vertical em Jogadores de Voleibol - dos Anjos, M. T. S.; Brasil, L. J.; de Oliveira Barros, B.; dos Santos Bastos, N. C.; de Souza Moraes, G. F. (Revista Brasileira de Medicina do Esporte, 2009)
In volleyball practice, ankle sprains represent 25 to 50% of the acute injuries. Preventive measures such as dynamic ankle bracing (DAB) are very often used; however, there is controversy on whether this would affect athletic performance or not. The aim of this study was to assess the effect of the Active Ankle System® (AAS) DAB on the vertical jump height in volleyball players. METHODS: The sample consisted of 14 female athletes aged between 14 and 18 years. The sample was told to jump, simulating the sportive gesture of attack and block (with and without DAB), over contact plates plugged to a notebook computer that calculated the height of the jump using a software. Previously, a pilot study was performed to establish the Intraclass Correlation Coefficient at the four testing conditions (n=4), and the outcomes were: attack with DAB 0.95; attack without DAB 0.76; block with DAB 0.92 and block without DAB 0.89. The height data from each sort of vertical jump with or without DAB were matched using paired Student's t test samples. RESULTS: To a significance level of a=0.05, no significant difference was found between the attack jumps with DAB (0.41 + 0.073m) and without DAB (0.41 + 0.086m), p=0.517. In addition, no significant difference was found between the block jumps with DAB (0.31 + 0.048m) and without DAB (0.32 + 0.050m), p=0.06. CONCLUSION: Therefore, the results of the present study point out that the use of the AAS DAB does not influence volleyball players' vertical jumping performance.